Araceae Spesies at Ornamental Plant Sales Points in Banda Aceh City - Chairun Nisa; Cut Nurmaliah; Hasanuddin Hasanuddin; Dewi Andayani; Djufri Djufri (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
Araceae is a plant that is known by the public, cultivated and traded to the people of Indonesia and is widely used as an ornamental plant. This study aims to determine the types of Araceae, and the types of Araceae that are most in demand at the point of sale of ornamental plants in Banda Aceh City. This research was conducted in November 2021. The methods used in this study were observation and interviews. The instruments used in this study were observation sheets and interviews. The data were analyzed descriptively qualitatively, that is, all data and information obtained in the field were collected and supported from relevant literature sources, displayed in tabular form and followed by interviews containing information about the types of Araceae, and the types of Araceae that were most in demand. at the point of sale of ornamental plants in Banda Aceh City. The results of the study found 25 species of Araceae. which consists of 13 genera Araceae, namely Aglaonema, Alocasia, Anthurium, Caladium, Colocasia, Dieffenbachia, Epipremnum, Hemalomena, Monstera, Scindapsus, Spathyphyllum, Syngonium, and Zantedeschia. The most popular Araceae species at the point of sale of ornamental plants in the city of Banda Aceh are Aglaonema with 19% enthusiasts and the least popular Araceae species with 2% interest are Colocasia, Epipremnun, Scindapsus, and Zantedeschia.Keywords: Araceae, Species, Ornamental Plants.Araceae merupakan tanaman yang di kenal oleh masyarakat, dibudidayakan dan diperjual belikan kepada masyarakat Indonesia serta banyak di manfaatkan sebagai tanaman hias. Penelitian ini bertujuan untuk mengetahui jenis-jenis Araceae, dan jenis-jenis Araceae yang paling diminati di tempat penjualan tanaman hias di Kota Banda Aceh. Metode yang digunakan dalam penelitian ini adalah observasi dan wawancara. Instrumen yang digunakan dalam penelitian ini adalah lembar observasi dan wawancara. Data dianalisis secara deskriptif kualitatif, yaitu semua data dan informasi diperoleh di lapangan yang terkumpul serta di dukung dari sumber literatur yang relevan ditampilkan dalam bentuk tabel dan dilanjutkan dengan wawancara yang berisi informasi tentang jenis-jenis Araceae, dan jenis-jenis Araceae yang paling diminati. di tempat penjualan tanaman hias di Kota Banda Aceh. Hasil penelitian ditemukan 25 spesies Araceae. yang terdiri dari 13 Genus Araceae yaitu Aglaonema, Alocasia, Anthurium, Caladium, Colocasia, Dieffenbachia, Epipremnum, Hemalomena, Monstera, Scindapsus, Spathyphyllum, Syngonium, dan Zantedeschia. Jenis Araceae yang paling diminati di tempat penjualan tanaman hias di kota Banda Aceh ialah Aglaonema dengan jumlah peminat 19% dan jenis Araceae yang sedikit diminati masyarakat dengan jumlah peminat 2% ialah Colocasia, Epipremnun, Scindapsus, dan Zantedeschia.Kata Kunci: Araceae, Spesies, Tanaman Hias.